2021
DOI: 10.1155/2021/5526327
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Hsp70 in Patients with Colorectal Cancer Patients: A PRISMA-Compliant Meta-Analysis

Abstract: Background. Hsp70 (heat shock protein 70) plays a key role in carcinogenesis and cancer progression. However, the relationship between the Hsp70 expression level and the colorectal cancer patient survival is unknown. This study is aimed at investigating the relationship between Hsp70 and the prognosis of colorectal carcinoma patients. Methods. PubMed, Web of Science, and Embase were used for systematic computer literature retrieval. Stata SE14.0 software was used for quantitative meta-analysis. Besides, data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Concerning CRC, the HSP70 overexpression has been described in comparison to non-neoplastic large bowel mucosa [60]. With a focus on impact on survival, a recent meta-analysis of nine studies presented worse prognosis in CRCs expressing HSP70, in line with our results [61]. Bauer et al, as above-mentioned, found HSP70 to be an unfavorable prognostic predictor, in line with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning CRC, the HSP70 overexpression has been described in comparison to non-neoplastic large bowel mucosa [60]. With a focus on impact on survival, a recent meta-analysis of nine studies presented worse prognosis in CRCs expressing HSP70, in line with our results [61]. Bauer et al, as above-mentioned, found HSP70 to be an unfavorable prognostic predictor, in line with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, it is overexpressed in number of cancers, although clinical data regarding CRC are, as observed by Gao at al. [37], surprisingly scanty. Lazaris et al [38] showed 77% of colorectal tumor samples to Oxicams downregulated expression of HSP90AA1 gene more markedly than protein: compounds #2-5 in Caco-2 cells and compounds #1-5 in HCT 116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, it is overexpressed in number of cancers, although clinical data regarding CRC are, as observed by Gao at al. [ 37 ], surprisingly scanty. Lazaris et al [ 38 ] showed 77% of colorectal tumor samples to contain at least 10% of neoplastic cells with Hsp70-immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the mechanisms and consequences of the interaction is essential. A potential key player of the crosstalk in the tumor microenvironment may be HSP70, which is overexpressed in cancer compared to normal tissue [ 2 , 79 , 80 , 81 , 82 ]. The expression was shown to be correlated to tumor grade, therapy resistance, and worse overall survival [ 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Role Of Exhsp70: Regulation Of Immune Responsesmentioning
confidence: 99%
“…A potential key player of the crosstalk in the tumor microenvironment may be HSP70, which is overexpressed in cancer compared to normal tissue [ 2 , 79 , 80 , 81 , 82 ]. The expression was shown to be correlated to tumor grade, therapy resistance, and worse overall survival [ 80 , 81 , 82 , 83 , 84 , 85 ]. In particular, HSP70 can inhibit the intrinsic and extrinsic apoptotic pathway and block oncogene-induced senescence, resulting in therapy resistance [ 2 ].…”
Section: Role Of Exhsp70: Regulation Of Immune Responsesmentioning
confidence: 99%